The burden of traditional neonatal uvulectomy among admissions to neonatal intensive care units, North Central Ethiopia, 2019: A triangulated crossectional study. - Wubet Alebachew Bayih; Biniam Minuye Birhan; Abebaw Yeshambel Alemu (PLoS ONE)
Background Traditional neonatal uvulectomy is unsupervised, unscientific and potentially dangerous cultural malpractice. It is often accompanied with life threatening neonatal morbidities such as infection, septicemia, anemia, aspiration and oropharyngeal injury. However, there is no current regional and even national data of its public health importance in the health care system. Therefore, this study was aimed at assessing the burden, associated factors and reasons of traditional uvulectomy among neonatal admissions at Debre Tabor General Hospital, North Central Ethiopia, from September 2018 to August 2019. Methods A quantitative cross sectional study supplemented with phenomenological study was employed on 422 mother-neonate pairs. Eight mothers who were not included in the quantitative part were involved as key informants of the qualitative study. Systematic and purposive sampling techniques were used to select study participants for the quantitative and qualitative parts of the study respectively. Multivariable logistic regressions were fitted to investigate significant predictors of traditional neonatal uvulectomy at p-value ≤ 0.05 and 95% CI. Moreover, the qualitative data were carefully transcribed, coded, screened, thematized, synthesized and then triangulated with the quantitative results. Results The burden of postuvulectomy admission was 67 (15.88%). Most of these admissions had post uvulectomy sepsis [59 (88.1%)] followed by anemia (55.23%). From multivariable analysis, factors that had significant odds of association with traditional neonatal uvulectomy include: having male neonate [AOR = 4.87; 95% CI: 1.10, 21.59], antenatal couple counseling about traditional neonatal uvulectomy [AOR = 0.053; 95% CI: 0.01, 0.35], home delivery [AOR = 6.02; 95% CI: 1.15, 31.61], postnatal couple counseling about traditional neonatal uvulectomy [AOR = 0.101; 95% CI: 0.02, 0.65], prior history of traditional neonatal uvulectomy [AOR = 7.15; 95% CI: 1.18, 43.21] and knowing at least one adverse effect of traditional neonatal uvulectomy [AOR = 0.068; 95% CI: 0.01, 0.44]. Furthermore, maternal perception of "there is no modern medicine to treat elongated and swollen neonatal uvula' was the most explained reason to practice traditional neonatal uvulectomy. Conclusion and recommendation The burden of traditional neonatal uvulectomy was high. Fortunately, its predictors are modifiable. Therefore, several advocacy teams of neonatal health consisting of mainly women health development armies, elders, religious fathers, health professionals and criminal prosecutors should be actively mobilized against traditional neonatal uvulectomy. Besides, parental couple counseling about the adverse effects of traditional neonatal uvulectomy should be properly implemented in the routine antenatal and postnatal continuum of care in South Gondar Zone, North Central Ethiopia.